2020
DOI: 10.3390/bios10120209
|View full text |Cite
|
Sign up to set email alerts
|

Review of Integrated Optical Biosensors for Point-of-Care Applications

Abstract: This article reviews optical biosensors and their integration with microfluidic channels. The integrated biosensors have the advantages of higher accuracy and sensitivity because they can simultaneously monitor two or more parameters. They can further incorporate many functionalities such as electrical control and signal readout monolithically in a single semiconductor chip, making them ideal candidates for point-of-care testing. In this article, we discuss the applications by specifically looking into point-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 125 publications
0
63
0
Order By: Relevance
“…This need asks for renovated fabrication strategies of point-of-care testing (POCT) devices, which show ease-of-use, compact size, and limited costs [118,119]. Many examples of already commercialized POCT have been reviewed recently and include pregnancy tests, glucose testing, and HIV testing [120]. LSPR-and SERS-based flexible biosensors are promising transducers for the design of a POCT due to the ease of integration with microelectronics and microfluidics [121] (Figure 6a).…”
Section: Promising Applications Of Flexible Biosensors 41 Point-of-care Testing For Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…This need asks for renovated fabrication strategies of point-of-care testing (POCT) devices, which show ease-of-use, compact size, and limited costs [118,119]. Many examples of already commercialized POCT have been reviewed recently and include pregnancy tests, glucose testing, and HIV testing [120]. LSPR-and SERS-based flexible biosensors are promising transducers for the design of a POCT due to the ease of integration with microelectronics and microfluidics [121] (Figure 6a).…”
Section: Promising Applications Of Flexible Biosensors 41 Point-of-care Testing For Disease Diagnosismentioning
confidence: 99%
“…More precisely, microfluidic channels must be highly transparent, to be compatible with light pathways, they should ensure an efficient sample delivery and minimize reagents and sample consumption [119]. On the other side, spectrometers and light sources (optical components) must be miniaturized to obtain a compact device and, although this is often not very easy, some methods to integrate LEDs for the transducer illumination and miniaturized spectrometers for the collection of the signal have been already proposed to overcome this issue [120]. POCTs for the diagnosis of disease especially in developing countries, where expensive laboratory equipment and specialized operators are not easily available are crucial for the rapid screening of a population.…”
Section: Promising Applications Of Flexible Biosensors 41 Point-of-care Testing For Disease Diagnosismentioning
confidence: 99%
“…SPR [94], interferometer [95], and microcavity [96] chips, as well as PhC [97,98] and fiber optic-type sensors [99], have all been integrated with microfluidic cells or other systems to create POC devices. The realization of these techniques into integrated, POCtype devices is mostly limited to research lab development, though some techniques have been commercialized [100]. argue that these types of integrated biosensors will act as key players in the future market of miniaturized, POC technology as their sensitivities, accuracy, and fabrication processes improve [100].…”
Section: Affinity-type Biosensors With Optical Signal Amplificationmentioning
confidence: 99%
“…A study showed optical biosensors based on a combined Mach–Zehnder interferometer. The methodology featured applying compatible microfluidics (COMS) to diagnose DNA without labeling [ 27 , 28 , 29 , 30 , 31 ]. Previous studies have reported the detection and classification of specific viruses via quantitative analysis and sorting of viruses and other particles in the micron and nanoparticle size ranges using light scattering and fluorescence measurements.…”
Section: Introductionmentioning
confidence: 99%